1. Write the equation:
d(-3 + x) = kx + 9
2. "Open" the parenthesizes:
-3d + dx = kx + 9
3. Take kx to the left side, -3d to the right, everything with different sign (+ replace with - when transferring, - replace with +):
dx - kx = 9 + 3d
4. Factor x in the left side:
x(d - k) = 9 + 3d
5. Finally, divide the whole equation by (d - k):
x = (9 + 3d)/(d - k)
That's the final answer. Good luck!
Answer:
False
Step-by-step explanation:
it has more than one dot in the same row, which means it has the same number more than once in the x - axis.
Answer:
i do not understand your question. do u want us to label from coldest to hottest?
Step-by-step explanation: